The relationship of university entrepreneurial orientation, academic innovation performance, and accreditation as moderation - Dewi Kusuma Wardani; Muhammad Sabandi; Feri Setyowibowo; Rizka Andriyati (Journal of Open Innovation: Technology, Market and Complexity)
This study investigates the empirical relationship between university entrepreneurial orientation (U-EO), accreditation, and academic innovation performance based on the concept of an entrepreneurial university. The purpose of this study is to determine whether academic innovation performance and U-EO are positively correlated, as well as whether accreditation can enhance this relationship. 489 Indonesian university departments participated in this study, which was conducted via random selection. The ENTRE-U scale is used for measuring U-EO, and the number of publications, patents, and spin-offs that lecturers produce is used to measure academic innovation performance. Hierarchical regression and econometric methods are used to test variable relationships. The results of this study show a positive correlation between academic innovation performance and U-EO. The performance of the department in generating publications, patents, and spin-offs can be improved by raising the U-EO. The positive correlation between academic innovation success and U-EO can be reinforced by accreditation. This study has implications for departments and universities seeking to maximize academic innovation performance through publications, patents, and spin-offs. This research adds insight into the entrepreneurial orientation of non-profit organizations, which still needs to be researched, there are universities, and strategies for improving their academic innovation performance as university entrepreneurial.